Policy For Formulation Of Criminal Sanctions Against Narcotics Criminal Offenders - Warsito Kasim (Gayaku Publisher, 2022)
In essence, narcotics are substances both natural and synthetic, namely narcotics, psychotropics and other addictive substances. If they enter the human body without following health regulations, they have an effect on the brain in the central structure and if misused, it is against legal provisions. Narcotics were first made by the British and then spread to mainland Asia, from China, Hong Kong, Japan to Indonesia.Examined from the optics of material criminal law, the Narcotics Law has several systems for formulating criminal sanctions (strafsoort) and several systems for formulating the duration of criminal witnesses (strafmaat). The system for formulating the length of criminal sanctions (strafmaat) is a fixed/definite sentence system in the form of a definite criminal threat, an indefinite sentence system in the form of a threat of a maximum length of sentence, then a determinate sentence system in the form of determining the minimum and maximum limits for the duration of a criminal threat and an indeterminate sentence system in the form of no the maximum criminal limit is determined. The law-making body completely delegates criminal policy (discretion) to criminal implementing officials at a lower level, for example in determining the size, nature or duration of punishment for perpetrators of certain crimes. The formulation system is indeterminate, determinate, presumptive and mandatory. Basically, according to criminal law science, there are several types of systems for formulating criminal sanctions (strafsoort), namely single/imperative formulation systems, alternative formulation systems, cumulative formulation systems, cumulative-alternative (mixed/combined) formulation systems and blind/blanch formulation systems. . Likewise, only for the system of formulating the length of criminal sanctions (strafmaat), there is a definite sentence system in the form of a threat of a definite length of sentence, a fixed/indefinite sentence system or maximum system, namely a threat of a maximum length of sentence, then a determinate sentence system in the form of a specified minimum limit and maximum criminal threat and indeterminate sentence system in the form of no specified maximum criminal limit, the law-making body gives full responsibility to criminal policy (decretion) to criminal implementing officials at lower levels, for example in determining the size, nature or duration of punishment for perpetrators certain crimes.